Málotřídní školy a faktory ovlivňující jejich existenci a fungování - Trnková, Kateřina, 1975- (2007)
In general, the existence and work of small schools with composite classes1 are often looked at ambiguously in education systems. It is therefore essential for them, what attitude takes the education policy towards them, whether they are rather supported or not. Each educational policy has to take account of many factors influencing the operation of each educational institution and reflect them in their standpoints and decisions. However, each of their levels, namely the national, regional and the local level, usually looks at the existence of small schools with composite classes differently. The dissertation thesis presents an analysis of the existing Czech educational policy towards small schools with composite classes. Four groups of factors influencing the existence of such small schools are analysed first. The factors are 1) educational, 2) demographic and geographical, 3) social and cultural, and 4) political and economic. The second, empirical part of the text analyses the Cze.